CO2 effect on catalytic abatement of VOC emissions over Cu-Co binary oxide films. (November 2021) - El Kasmi, Achraf; Waqas, Muhammad; Wu, Ling-Nan; Arshad, Muhammad Fahad; Tian, Zhen-Yu
Highlights: Catalysts exhibited good activity for C2 H2 and C3 H6 decompositions at high GHSV. The catalysts' capability in the presence of CO2 effect was investigated here. Slight-promoted Co3 O4 catalyst with Cu element resulted in the highest catalytic activity. High Cu-doping Co3 O4 revealed an enhancement of the reaction stability on-stream. DFT calculations demonstrated Cu is an active site and CO2 is an inhibitor. Abstract: The control of Cu loading in Co3 O4 structure was used as noble-free thin-film catalysts for efficient short-chain VOC (volatile organic compound) emissions treatment. All catalysts were capable to decompose C2 H2 and C3 H6 at high gas hourly space velocity. Slight-promoted Co3 O4 catalyst with Cu element resulted in the highest catalytic activity owing to the improved active surface oxygen amount and the high dispersion of Cu. High amount of Cu-loading in the cobalt oxide exhibited a more enhancement of the reaction stability on-stream due to high density of the active phase at the surface. The CO2 effect was investigated. Using DFT (density function theory) calculations, Cu exhibited an active site for C3 H6 and C2 H2 adsorption, and CO2 could react as an inhibitor in the adsorption process. Such strategy of tailoring the activity and stability-on-stream through the control of Cu-promoting oxide catalysts could establish a promising way to improve the catalytic performance towards gas emissions control. Graphical abstract: Image, graphical abstract